Exploring the Relationship Among International Students' English Self-efficacy, Using English to Learn Self-efficacy, and Academic Self-efficacy - Wang, Chih-hsuan; Harrison, Jamie; Cardullo, Victoria; Lin, Xi (Journal of International Students, 2018)
One of the major challenges for international students to pursue academic goals in the United States is English language proficiency, which often negatively affects academic success. Even students with confidence in their English language proficiency encounter challenges using English in class. Previous research indicates self-efficacy positively predicts English language proficiency and academic achievement. Therefore, the current study hypothesized a model using self-efficacy in using English to learn as a mediator between English and academic self-efficacy. The structural equation modeling results indicate English self-efficacy indirectly influenced international students’ academic self-efficacy through their using English to learn self-efficacy. Findings suggest using English and using English to learn self-efficacy are two distinct constructs. These results warrant academic English support for non-native English speaking international students.